Manual reload organization in military transportation - Vitomir Miladinović (Vojnotehnički Glasnik, 1997)
Manual reload in transportation is important for all types of transport, especially when the supply chain is broken in war conditions. As a specific field of activity, it has its own technological process laws as well as methods for planning the optimal use of transportation means and man power. An important factor is a choice and use of improvised tools and devices, which attributes to increased productivity and human engineering. The knowledge of basic principles of work technology and organization is important for administration officers in the reload planning phase as well as for executive officers in the realization phase.